Effect of artificial tears on automated visual field testing in patient with glaucoma and dry eye syndrome - كرّوم رنيم; تيم درويش; محمود رجب (Latakia University Journal -Medical Sciences Series, 2023)
Purpose: To examine the effect of a single dose of artificial tear administration on automated visual field (VF) testing in patients with glaucoma and dry eye syndrome. Study type: cross-sectional study. Material and Methods: Fifty patients (50 sample eyes/50 control eyes) suffering bilateral primary open-angle glaucoma with an experience in visual field test and dry eye syndrome were enrolled in this study. A computerized visual field examination was performed with the Octupus 900 G program for both eyes, then repeated after 15 minutes, after instillation of artificial tears in the right eye only, while the left eye remained as a control. Reliability criteria and visual field indices were compared between the two examinations before and after instillation. Results: Our study shows that the administration of a single dose of artificial tears significant improvement in the values of MD, examination duration, false positive, false negative, and reliability factor (p < 0.0001), with a slight improvement in sLV values, but without any statistical significance ( p>0.08). Conclusion: A single dose of artificial tear administration immediately before VF testing in POAG patients with dry eye syndromes seems to improve test results and decrease test time.